Analisis Dan Perancangan E-Service Untuk Pelanggan Pada Jaya Bersama Konveksi - Rosmiati - AMIK BSI Pontianak, Mia (Indonesian Journal on Software Engineering (IJSE), 2015)
Jaya Bersama Convection is a home industry engaged in the production of uniform and is currently growing interest. Increasingly widespread marketing is done by Jaya Bersama Convection more the potential prospects who will use the services at the Jaya Bersama Convection in the manufacture of uniforms. This leads to Jaya Bersama Convection must always provide the best service to its customers and prospective customers. In this research will be focused on designing applications that can help Jaya Bersama Convection in providing the best service untu customers. Eservice is an application that is capable of providing all the information available at the Jaya Bersama Convection, in particular to provide information required by the customer or prospective customer. So as to facilitate the owner Jaya Bersama Convection provide information to customers or prospective customers. And also allows the owner in the process of marketing and product introduction to the wider community.Â Keywords: eService, Information Systems